2002
DOI: 10.1090/s0002-9939-02-06413-4
|View full text |Cite
|
Sign up to set email alerts
|

Local indicability in ordered groups: Braids and elementary amenable groups

Abstract: Abstract. Groups which are locally indicable are also right-orderable, but not conversely. This paper considers a characterization of local indicability in right-ordered groups, the key concept being a property of right-ordered groups due to Conrad. Our methods answer a question regarding the Artin braid groups Bn which are known to be right-orderable. The subgroups Pn of pure braids enjoy an ordering which is invariant under multiplication on both sides, and it has been asked whether such an ordering of Pn co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…1 An important result of Dehornoy [8] (see also [13] and [29]) is that the full braid groups B n can be given a strict total ordering which is invariant under multiplication on one side (but not both). We will see that Dehornoy's ordering of B n and our ordering of P n are fundamentally incompatible; indeed any right-or left-ordering of B n is necessarily incompatible with any bi-ordering of P n , according to [27].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1 An important result of Dehornoy [8] (see also [13] and [29]) is that the full braid groups B n can be given a strict total ordering which is invariant under multiplication on one side (but not both). We will see that Dehornoy's ordering of B n and our ordering of P n are fundamentally incompatible; indeed any right-or left-ordering of B n is necessarily incompatible with any bi-ordering of P n , according to [27].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 92%
“…Recently, Rhemtulla and Rolfsen [27] have shown that no right-or left-invariant ordering of B n whatsoever can be bi-invariant when restricted to P n , or any other finite index subgroup.…”
Section: Theorem 17mentioning
confidence: 99%
“…In [1] (see also [2]), J. Howie shows that the classes of locally indicable groups and right orderable groups are quasivarieties and he also asserts that the class of locally indicable groups is a subclass of the class of right orderable groups. He posed the question of whether or not these two classes coincide.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we show that each of the quasi-varieties of orderable groups and right-orderable groups has undecidable theory. Since the paper of Howie, there has been a significnat amount of work on orderable groups (See [2] [3] [4] and the references there). We note the classic result that free groups are orderable.…”
Section: Introductionmentioning
confidence: 99%
“…every non-trivial finitely generated subgroup admits an epimorphism onto Z), and locally indicable groups are right-orderable (i.e. admit a total order which is invariant under right multiplication), see Rhemtulla-Rolfsen [15]. Some families of Artin groups are known to be poly-free.…”
Section: Introductionmentioning
confidence: 99%